2022
DOI: 10.3390/plants11233337
|View full text |Cite
|
Sign up to set email alerts
|

Growth, Biomass Partitioning, and Photosynthetic Performance of Chrysanthemum Cuttings in Response to Different Light Spectra

Abstract: Chrysanthemum (Chrysanthemum morifolium) is among the most popular ornamental plants, propagated mainly through stem cuttings. There is a lack of information regarding the impact of the lighting environment on the successful production of cuttings and underlying mechanisms. The light spectrum affects plant morphology, growth, and photosynthesis. In the present study, chrysanthemum, cv. ‘Katinka’ cuttings, were exposed to five lighting spectra, including monochromatic red (R), blue (B) lights, and multichromati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 62 publications
0
6
0
Order By: Relevance
“…For example, the hypocotyls of Arabidopsis and tomato grown under red light are longer than those grown under blue light [ 18 ]; the chlorophyll content in leaves of rice seedlings grown under red light is lower than that under blue light [ 19 ]. The regulation of red and blue light for plant growth and development also differs between species: for example, the hypocotyls of cucumber grown under blue light are longer than those under red light [ 20 ]; the chlorophyll concentration in leaves from chrysanthemum grown under red and blue light is not significantly different [ 21 ]. However, the effects of different light qualities on the growth of moso bamboo seedlings have not been reported.…”
Section: Introductionmentioning
confidence: 99%
“…For example, the hypocotyls of Arabidopsis and tomato grown under red light are longer than those grown under blue light [ 18 ]; the chlorophyll content in leaves of rice seedlings grown under red light is lower than that under blue light [ 19 ]. The regulation of red and blue light for plant growth and development also differs between species: for example, the hypocotyls of cucumber grown under blue light are longer than those under red light [ 20 ]; the chlorophyll concentration in leaves from chrysanthemum grown under red and blue light is not significantly different [ 21 ]. However, the effects of different light qualities on the growth of moso bamboo seedlings have not been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Increase in anthocyanins content (2,19) and storage carbohydrates ( 19) by R light have been reported in rose and savory plants. Furthermore, increase in the amount of carotenoids and soluble carbohydrates by R light has been also reported in chrysanthemum cuttings (32). The ndings on the reproductive characteristics showed that by using supplemental light, marketability can be increased, which is more highlighted in plants exposed to R90B10 supplemental light treatments.…”
Section: 3mentioning
confidence: 72%
“…Usually, light absorption and capture by the plant are mediated by intracellular pigments. The ability of light-sensitive pigments, such as chlorophylls, carotenoids, and anthocyanins, to capture and absorb light is influenced by various factors, such as the light intensity, light quality, and light duration [22]. When intense light exposure exceeds the light energy absorbed and utilized by chlorophyll, the plant is in a state of excess light energy, which initiates a non-radiative energy dissipation pathway to consume the excess excitation energy.…”
Section: Discussionmentioning
confidence: 99%